2018
DOI: 10.1177/0197918318806891
|View full text |Cite
|
Sign up to set email alerts
|

Class Background, Reception Context, and Intergenerational Mobility: A Record Linkage and Surname Analysis of the Children of Irish Immigrants

Abstract: Proponents of restrictive immigration policies often claim that families arriving with fewer skills and resources will struggle economically. This claim is challenging to test as lower-skilled migrants also tend to face greater discrimination, exclusion, and obstacles in the United States. I use unique multigenerational data on Irish Americans in the early-twentieth century, before and after migration, to directly study how the economic origins of Irish families and the reception context they faced in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Similarly, immigrants enter new racial/ethnic hierarchies that may place individuals and groups in less desirable positions. The local labor market context, where immigrants transfer their premigration skills, may also reward certain positions and groups over others (Connor 2018b). At the same time, endogenous contextual influences deriving from the society of origin, such as its cultural, political, or economic conditions, influences the first generations' environment in which they grew up.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, immigrants enter new racial/ethnic hierarchies that may place individuals and groups in less desirable positions. The local labor market context, where immigrants transfer their premigration skills, may also reward certain positions and groups over others (Connor 2018b). At the same time, endogenous contextual influences deriving from the society of origin, such as its cultural, political, or economic conditions, influences the first generations' environment in which they grew up.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Since immigrants with lower status backgrounds often entered manufacturing, the sectors would have lifted them up to positions similar to those with a higher status background who did not enter manufacturing sectors. Empirical work analyzing the importance of manufacturing, however, has shown that these sectors had little effect in producing mobility for both the first and second generations (Catron 2016;Waldinger 2007;Connor 2018b). Indeed, first generation immigrants who entered manufacturing firms ended their careers in positions similar to what they startedpositions at the bottom (Catron 2016).…”
Section: The Melting-pot In the Age Of Mass Migrationmentioning
confidence: 99%
See 3 more Smart Citations